2022
DOI: 10.3168/jds.2021-21450
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for dairy calf and replacement heifer wellness traits and their association with cow longevity and health indicators in Holstein cattle

Abstract: High mortality and involuntary culling rates cause great economic losses to the worldwide dairy cattle industry. However, there is low emphasis on wellness traits in replacement animals (dairy calves and replacement heifers) during their development stages in modern dairy cattle breeding programs. Therefore, the main objectives of this study were to estimate genetic parameters of wellness traits in replacement cattle (replacement wellness traits) and obtain their genetic correlations with 12 cow health and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Murray (2011) reported that calf mortality in Canada ranged between 7% and 11%, and 53% of calf mortality was attributed to diarrhea and 21% to respiratory illness. Consequently, many international efforts have aimed at estimating genetic parameters for calf health traits (Heringstad et al 2008;Fuerst-Waltl et al 2010;Henderson et al 2011aHenderson et al , 2011bMcCorquodale et al 2013;Gonzalez-Peña et al 2019;Johnston et al 2020;Zhang et al 2022), showing low heritability for calf diarrhea (range: 0.03-0.06), calf respiratory illness (range: 0.04-0.09), and calf mortality (range: 0.001-0.12). This suggests that selection for these traits is possible, but, with the exception of the Clarifide Plus product (Zoetis 2018) and the new Calf Immunity Index (Semex 2022), the incorporation of these traits in routine genetic evaluations is limited to date.…”
Section: Introductionmentioning
confidence: 99%
“…Murray (2011) reported that calf mortality in Canada ranged between 7% and 11%, and 53% of calf mortality was attributed to diarrhea and 21% to respiratory illness. Consequently, many international efforts have aimed at estimating genetic parameters for calf health traits (Heringstad et al 2008;Fuerst-Waltl et al 2010;Henderson et al 2011aHenderson et al , 2011bMcCorquodale et al 2013;Gonzalez-Peña et al 2019;Johnston et al 2020;Zhang et al 2022), showing low heritability for calf diarrhea (range: 0.03-0.06), calf respiratory illness (range: 0.04-0.09), and calf mortality (range: 0.001-0.12). This suggests that selection for these traits is possible, but, with the exception of the Clarifide Plus product (Zoetis 2018) and the new Calf Immunity Index (Semex 2022), the incorporation of these traits in routine genetic evaluations is limited to date.…”
Section: Introductionmentioning
confidence: 99%